National collections, global collecting: the responsibilities of librarians as collectors - Prochaska, A (University of Texas Press, 2002)
Sharing knowledge, while not a new concept, is receiving new emphasis in a global society. National and other research libraries can fruitfully collaborate to maximize the public value of their materials. The partnership of the British Library with the Ramsom Center is one example of this.